Rabbits' eye globe sonographic biometry - Toni, Maria Carolina [UNESP]; Wilkes Burton Meirelles, Adriana Erica [UNESP]; Gava, Fabio Nelson [UNESP]; Camacho, Aparecido Antonio [UNESP]; Laus, Jose Luiz [UNESP]; Canola, Julio Carlos [UNESP] (Wiley-Blackwell, 2010)
ObjectiveTo measure intraocular structures in New Zealand White breed rabbits (Oryctolagus cuniculus Linnaeus, 1758) using A-mode and B-mode ultrasound with a 20 MHz transducer.ProceduresIn this study, the eyes of 15 rabbits were evaluated for determination of intraocular measurements using an ophthalmic ultrasound unit able to operate in both A and B-modes. The distances from the cornea to the anterior capsule of the lens (D1), from the anterior capsule of the lens to the posterior capsule of the lens (D2), from the posterior capsule of the lens to the retina (D3) and the complete length of the eye, which corresponds to the distance from the cornea to the retina (D4) were taken.ResultsThe mean values obtained were 2.70 mm (+/- 0.22 mm) for D1, 7.32 mm (+/- 0.40 mm) for D2, 7.10 mm (+/- 0.45 mm) for D3 and 17.12 mm (+/- 0.41 mm) for D4. Statistical analyses using the Student's t-test showed that there were no differences between the eyes.ConclusionsThe study was feasible without the need of pharmacological restraint and yielded normal mean values for ocular sonographic biometry in rabbits.
Keywords: biometry; eyes; Rabbits; Ultrasound